Many hops, many stops: care-seeking “loops” for diabetes and hypertension in three urban informal settlements in the Mumbai Metropolitan Region - Ramani, Sudha; Bahuguna, Manjula; Spencer, Jennifer; Pathak, Sweety; Shende, Sushma; Pantvaidya, Shanti; D’Souza, Vanessa; Jayaraman, Anuja (Frontiers in Public Health, 2024)
Background The burden of Non-Communicable Diseases (NCDs) in urban informal settlements across Lower and Middle Income Countries is increasing. In recognition, there has been interest in fine-tuning policies on NCDs to meet the unique needs of people living in these settlements. To inform such policy efforts, we studied the care-seeking journeys of people living in urban informal settlements for two NCDs—diabetes and hypertension. The study was done in the Mumbai Metropolitan Region, India. Methods This qualitative study was based on interviews with patients having diabetes and hypertension, supplemented by interactions with the general community, private doctors, and public sector staff. We conducted a total of 47 interviews and 6 Focus Group Discussions. We synthesized data thematically and used the qualitative software NVivo Version 10.3 to aid the process. In this paper, we report on themes that we, as a team, interpreted as striking and policy-relevant features of peoples’ journeys. Results People recounted having long and convoluted care-seeking journeys for the two NCDs we studied. There were several delays in diagnosis and treatment initiation. Most people’s first point of contact for medical care were local physicians with a non-allopathic degree, who were not always able to diagnose the two NCDs. People reported seeking care from a multitude of healthcare providers (public and private), and repeatedly switched providers. Their stories often comprised multiple points of diagnosis, re-diagnosis, treatment initiation, and treatment adjustments. Advice from neighbors, friends, and family played an essential role in shaping the care-seeking process. Trade-offs between saving costs and obtaining relief from symptoms were made constantly. Conclusion Our paper attempts to bring the voices of people to the forefront of policies on NCDs. People’s convoluted journeys with numerous switches between providers indicate the need for trusted “first-contact” points for NCD care. Integrating care across providers—public and private—in urban informal settlements—can go a long way in streamlining the NCD care-seeking process and making care more affordable for people. Educating the community on NCD prevention, screening, and treatment adherence; and establishing local support mechanisms (such as patient groups) may also help optimize people’s care-seeking pathways.